Surfactant‐assisted hydrothermal preparation of monoclinic bismuth vanadate microspheres and visible‐light‐driven photocatalytic activity. (1st November 2013) - Wang, Xinjun; Liu, Huanli; Wan, Xiaoli
Abstract : Beautiful monoclinic bismuth vanadate (BiVO4 ) microspheres have been fabricated by using the sodium dodecyl sulphate (SDS) assisted hydrothermal strategy with bismuth nitrate and ammonium metavanadate as a metal source. The physicochemical properties of the materials were characterised by means of X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, Brunauer‐Emmett‐Teller and UV–vis techniques. The photocatalytic activities of the as‐fabricated BiVO4 microspheres were measured for the photodegradation of methylene blue under visible‐light irradiation. The effects of SDS on the synthesis of BiVO4 microspheres were investigated. Comparison experiments were conducted and showed that the amount of SDS significantly influences the morphology of the products. The possible formation mechanism of such BiVO4 microsphere material is also discussed.